Conventional and Virtual Reality Mirror Therapies in Upper Obstetric Brachial Palsy: A Randomized Pilot Study - Yeves-Lite, Alba (J Clin Med, 2020)
The abilities of children diagnosed with Obstetric Brachial Palsy (OBP) are limited by brachial plexus injuries. Thus, their participation in the community is hindered, which involves a lower quality of life due to worse performance in activities of daily living as a consequence of the functional limitations of the affected upper limb. Conventional Mirror Therapy (Conventional MT) and Virtual Therapy improve the affected upper limb functionality. Therefore, the aim of this study was to compare the effects of Conventional MT and Virtual Reality MT on the spontaneous use of the affected upper limb and quality of life of children with upper Obstetric Brachial Palsy between 6 and 12 years of age. A randomized pilot study was performed. Twelve children were randomly assigned to perform Conventional Mirror Therapy or Virtual Reality Mirror Therapy for four weeks. Ten children completed the treatment. Two assessments (pre/post-intervention) were carried out to assess the spontaneous use of the affected upper limb and the quality of life using the Children’s Hand-use Experience Questionnaire (CHEQ) and the Pediatric Quality of Life Inventory Generic Core Scales (PedsQL TM 4.0), respectively. There was a statistically significant increment in spontaneous use, observed in independent tasks (p = 0.02) and in the use of the affected hand with grasp (p = 0.04), measured with the CHEQ, for the Virtual Reality MT group. There were no statistically significant changes (p > 0.05) for the Conventional MT group in the spontaneous use of the affected upper limb. Regarding the quality of life, statistically significant changes were obtained in the Physical and Health activity categories of the parents’ questionnaire (p = 0.03) and in the total score of the children’s questionnaire (p = 0.04) in the Virtual Reality MT group, measured using the PedsQL TM 4.0. Statistically significant changes were not obtained for the quality of life in the Conventional MT group. This study suggests that, compared to Conventional MT, Virtual Reality MT would be a home-based therapeutic complement to increase independent bimanual tasks using grasp in the affected upper limb and improve the quality of life of children diagnosed with upper OBP in the age range of 6–12 years.